The effects of Teucrium polium on ionizing radiation-induced intestinal damage in rats - Demirel, U.; Harputluoglu, M. M. M.; Us, S. B.; Kaya, E.; Sahin, N.; Aydin, N. E.; Aladag, M. (Univ Catholique Louvain-Ucl, 2011)
Background and study aims : Oxidative stress plays an important role in development of intestinal injury after abdomino-pelvic radiation therapy. Teucrium poliuin (TP) is a medicinal plant which has antioxidant and anti-inflammatory properties. The aim of this study was to investigate the effect of TP on radiation-induced intestinal oxidative damage in rats. Materials and methods : Group 1 (n = 8), the control group; Group 2 (n = 8), the RAD (radiation) group in which each rat received a single whole-body 800 cGy radiation performed with a LINAC; Group 3 (n = 8), the RAD + TP group in which rats were exposed to radiation as in Group 2, followed by intragastric administration of 0.5 g/kg/daily TP extract for 7 consecutive days; and Group 4 (n = 8), the TP group, rats received only intragastric TP for 7 days. Results : Radiation led to intestinal damage, which was accompanied by an increase in intestinal thiobarbituric-acid-reactive substances (TBARS) and myeloperoxidase (MPO) levels, and a decrease in reduced glutathione (GSH) levels. Although TP significantly decreased intestinal MPO levels and inflammation scores, it neither reverted intestinal TBARS and GSH levels nor ameliorated other histological parameters of the disease. Conclusions : Our results suggest that TP reduces inflammation but does not ameliorate the increased oxidative stress conditions in radiation-induced intestinal damage in rats. (Acta gastroenterol. belg., 2011, 74, 491-496).
Keywords: Teucrium polium; radiation; intestine; oxidative stress; inflammation